2018
DOI: 10.21273/hortsci13410-18
|View full text |Cite
|
Sign up to set email alerts
|

The Profitability of New Citrus Plantings in Florida in the Era of Huanglongbing

Abstract: The Florida citrus industry has been enduring the impact of citrus greening since 2005. The disease has been the main driver for the state's citrus production to plummet by 80% in the past 13 years, causing the industry to downsize drastically. Planting new groves is key to ensuring a supply of fruit for processors and packinghouses to stay in business. However, a key question is whether it makes economic sense to plant a new grove in the current environment. We estimate the establishment and production costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 4 publications
0
31
0
Order By: Relevance
“…citri were discovered in Florida in 1998 and HLB-symptomatic trees were later discovered in Florida in 2005 [1]. The disease has since devastated the Florida citrus industry with consistent reductions year-after-year in citrus acreage and historically low citrus production [9,10]. The majority of citrus trees in Florida are now infected with CLas [11].…”
Section: Introductionmentioning
confidence: 99%
“…citri were discovered in Florida in 1998 and HLB-symptomatic trees were later discovered in Florida in 2005 [1]. The disease has since devastated the Florida citrus industry with consistent reductions year-after-year in citrus acreage and historically low citrus production [9,10]. The majority of citrus trees in Florida are now infected with CLas [11].…”
Section: Introductionmentioning
confidence: 99%
“…Florida has lost >60% of citriculture acreage, >80% of production, and >70% of its juice plants and fresh fruit packinghouses. If not curtailed, the persistent decline could destroy the Florida citrus industry, previously the second largest globally (8,(13)(14)(15).…”
mentioning
confidence: 99%
“…Previous studies have also demonstrated that high-density plantings result in greater production per area [53,54] especially under HLB-endemic conditions [9,16]. New groves planted at higher densities in Florida can be more profitable than groves planted at low densities [7,14]. Additionally, as grove production costs increase, higher density plantings have become a global trend [15].…”
Section: Number Of Fruit Fruit Size and Fruit Yieldmentioning
confidence: 99%